Artificial Intelligence Policy in Promoting Indonesian Tourism - Jaelani, Abdul Kadir; Luthviati, Resti Dian; Siboy , Ahmad; Al Fatih, Sholahuddin; Hayat, Muhammad Jihadul (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2024)
Artificial intelligence changes how tourist destinations operate, provides better service to visitors, and provides long-term benefits for local communities and the environment. However, it is essential to question whether governments can effectively resolve data privacy and cybersecurity challenges when deploying these technologies. This study aims to analyze issues related to the role of artificial intelligence policy in promoting Indonesia's digital tourism. This research employs a normative legal approach, drawing from both statutory and historical sources. This research concludes that Indonesia promotes artificial intelligence in tourism by investing in AI technology research and development, collaborating between the government and the private sector to implement AI solutions, and establishing a supportive regulatory framework to ensure the ethical use of AI in tourism. The impact of digitalization policies on digital tourism includes increasing accessibility and convenience for tourists through online ordering systems and digital payment methods, developing smart destinations with Internet of Things technology and data-based insights, and enhancing tourist experiences through augmented reality applications and virtual reality.